2013
DOI: 10.1038/bjc.2013.315
|View full text |Cite
|
Sign up to set email alerts
|

Mammaglobin B (SCGB2A1) is a novel tumour antigen highly differentially expressed in all major histological types of ovarian cancer: implications for ovarian cancer immunotherapy

Abstract: Background:We studied the genetic fingerprints of ovarian cancer and validated the potential of Mammaglobin b (SCGB2A1), one of the top differentially expressed genes found in our analysis, as a novel ovarian tumour rejection antigen.Methods:We profiled 70 ovarian carcinomas including 24 serous (OSPC), 15 clear-cell (CC), 24 endometrioid (EAC) and 7 poorly differentiated tumours, and 14 normal human ovarian surface epithelial (HOSE) control cell lines using the Human HG-U133 Plus 2.0 chip (Affymetrix). Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…In a recent study by Tassi, mammaglobin B was found to be highly overexpressed in nearly 50% of ovarian cancer specimens and high level expression independently correlated with a better outcome [198-200]. Bellone and colleagues [201] subsequently showed that it was highly immunogenic as can generate robust antibody responses and containing T cell epitopes.…”
Section: Targeted Antigens In Ovarian Cancermentioning
confidence: 99%
“…In a recent study by Tassi, mammaglobin B was found to be highly overexpressed in nearly 50% of ovarian cancer specimens and high level expression independently correlated with a better outcome [198-200]. Bellone and colleagues [201] subsequently showed that it was highly immunogenic as can generate robust antibody responses and containing T cell epitopes.…”
Section: Targeted Antigens In Ovarian Cancermentioning
confidence: 99%
“…Claudin-3/4 were recently found by our group as well as others to be preferentially overexpressed in multiple histological types of ovarian cancer 912 . Interestingly, these receptors were found to be more expressed in chemotherapy-resistant ovarian cancers when compared to chemotherapy-naïve ovarian tumors as well as in the subpopulation of CD44-positive cancer cells with stem cells properties, thought to be responsible for the development of drug resistance and tumor relapse 13, 14, 2615 .…”
Section: Discussionmentioning
confidence: 59%
“…Our research group has analyzed the genetic fingerprints of a large number of epithelial ovarian cancers 912 . In these studies we discovered Claudin-3 and Claudin-4 as two of the top differentially expressed genes in all histological ovarian cancer types tested 912 .…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancers of varying subtypes including mucinous, serous, undifferentiated, clear cell, and endometrioid carcinomas have been found to highly express claudin-3 and claudin-4 but normal ovarian surface epithelium does not [14,59,8183] (Table 2). This data suggests that the low-level expression of these claudins is associated with a benign condition and that high expression is more likely to be a signal of a malignant transformation.…”
Section: Claudins In Ovarian Cancermentioning
confidence: 99%